2012
DOI: 10.1590/s0102-44502012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Uma análise sistêmico-funcional do dizer em artigos científicos de graduandos

Abstract: Resumo: Os processos verbais são o foco de nossa análise para investigar a forma como o dizer é construído em artigos acadêmicos produzidos por alunos de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A fair amount of research on reported speech and on reporting verbs in Portuguese focuses on journalistic (Corbari and Ramos 2018) or literary registers (Saburi Costa and Freitas 2017), and there has been little research on this phenomenon in academic language. Most studies in academic Portuguese analyze reporting practices more broadly (Hoffnagel 2010;Bessa 2011), with few studies focusing on reporting verbs other than some isolated hints here and there (Souza and Mendes 2012). Bessa (2011) discusses the use of reporting verbs as a mandatory practice in academia, as an academic piece of writing is only valid when including arguments and theories discussed by other authors.…”
Section: Reported Speech In Portuguesementioning
confidence: 99%
“…A fair amount of research on reported speech and on reporting verbs in Portuguese focuses on journalistic (Corbari and Ramos 2018) or literary registers (Saburi Costa and Freitas 2017), and there has been little research on this phenomenon in academic language. Most studies in academic Portuguese analyze reporting practices more broadly (Hoffnagel 2010;Bessa 2011), with few studies focusing on reporting verbs other than some isolated hints here and there (Souza and Mendes 2012). Bessa (2011) discusses the use of reporting verbs as a mandatory practice in academia, as an academic piece of writing is only valid when including arguments and theories discussed by other authors.…”
Section: Reported Speech In Portuguesementioning
confidence: 99%